Vertical momentum transport over mountainous terrain - Wooldridge, Gene L., author; Reiter, Elmar R., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1970)
High-resolution pictures obtained with a handheld camera during the earth-orbital photographic mission of the Apollo IX spacecraft provided a unique opportunity to map the areal extent of gravity waves over the southwestern United States. The orientation of cumulus streets and cirrus streaks augmented conventional wind data for momentum and kinetic energy calculations. Zonal shearing stress gradients in stably stratified air flowing over rugged mountainous terrain indicated very large subgrid-scale vertical fluxes of zonal momentum. Maximum stress values of several tens of dynes cm-2 occurred in the lower tropospheric layers where the air flow encountered the high Rocky Mountains of central New Mexico. The vertical fluxes of zonal momentum were directed upward to tropopause levels when extensive areas of gravity waves covered eastern Arizona, New Mexico, and western Texas. The potential energy contained in the wave population 5-2 attained values through the troposphere as high as 9.3 x 10 joules m 8-2 (9.3 x 10 ergs cm); this potential energy apparently played a substantial role in the energy budget. The residual "dissipation" term in the kinetic energy budget indicated a subgrid-scale flux of energy downward from the lower stratosphere concurrent with the upward flux of zonal momentum. Atmospheric turbulence rose to a maximum intensity during the wave occurrence, diminishing gradually thereafter.
CER70-71GLW28.
September, 1970.
This report was prepared with support under contract number NAS 9-10305 National Aeronautics and Space Administration.
Keywords: Gravity waves; Atmospheric circulation -- Effect of mountains on